Cooling slope casting of AA7075 alloy combined with reheating and thixoforging - Guler, Kerem Altug; Kisasoz, Alptekin; Ozer, Gokhan; Karaaslan, Ahmet (ELSEVIER, 2019)
Cooling slope casting has been applied to aluminium casting alloys for producing ingots with non-dendritic microstructure. Semi-solid forming of the AA7075 was studied via cooling slope casting, reheating and thixoforging processes in order to determine the effect of semi-solid casting on the microstructure of the alloy. AA7075 ingots with non-dendritic microstructure were produced with cooling slope pouring. Castings were characterized by light microscopy, image analysis, scanning electron microscopy and EDS analysis. The resulting structures are promising in terms of grain size and sphericity. It was realized that grain coarsening may occur very suddenly in the reheating process. Cooling slope castings were obtained with 30 degrees and 60 degrees inclination angles, and in comparison, 60 degrees castings showed better results. Moreover, by using short reheating periods, semi-solid forging causes trace formation in the solid grains.
Keywords: semi-solid alloy; cooling slope casting; thixoforging; AA7075 alloy; 7075 ALUMINUM-ALLOY; MG-CU ALLOY; MICROSTRUCTURAL EVOLUTION; MECHANICAL-PROPERTIES; PARAMETERS; ECAP; SIMA; SC; Metallurgy & Metallurgical Engineering